Laboratory hands-on activity: A case study in senior high school of Pekanbaru-Indonesia - Maysi Hidayah Ramadhani; Prima Wahyu Titisari (University of Muhammadiyah Malang, 2019)
The issues arise in performing laboratory hands-on activity are: the less frequence in its implementation, the lack of students interest, the limited in time, and lack of preparation. By considering the importance of laboratory hands-on activity, it is necessary to examine the conditions of the hands-on activity in school whether the activity has been in accordance with the existing rules and standards. This study aimed to determine the implementation of biology hands-on activity in students’ grade XI of SSHS 10-Pekanbaru. The population in this study was 144 students. The sampling technique used were Slovin formula and purposive sampling, in which the sample was 60 students of class XI MIPA-1 to MIPA-4. The instruments used to collect the data in this study were questionnaires, observation sheets, and interviews. The results showed that the for 4 indicators observed (i.e. hands-on activity intensity, students’ interest in hands-on activity, hands-on activity duration, and hands-on activity preparation) reached the percentages between 76.14% and 80.66%, which were in the good category. Thus, it can be concluded that this school has been conducting a good hands-on activity. It is suggested for further researchers to focus on problems analysis and alternative solutions